2015
DOI: 10.20452/pamw.3172
|View full text |Cite
|
Sign up to set email alerts
|

Flexible bronchoscopy under conscious sedation with midazolam and fentanyl can be safely performed by nonanesthesiologists

Abstract: RESEARCH LETTER Flexible bronchoscopy under conscious sedation with midazolam and fentanyl... 869contraindications to use midazolam or fentanyl, diminished communication capacity, and cognitive disorders. The study was approved by the Ethics Committee at Jagiellonian University, Kraków, Poland.In all patients, topical anesthesia was used according to current guidelines. 4 Most patients received a bolus of midazolam (2.5 mg) and fentanyl (0.05 mg) before the examination. If necessary, both medications were titr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
4
6
0
Order By: Relevance
“…The American College of Chest Physicians and BTS guidelines recommend diagnostic flexible bronchoscopy under conscious sedation (4,5). Bronchoscopy under conscious sedation with a combination of midazolam with fentanyl in this study could be safely performed and confirmed the previous study (12). Conscious sedation may lead to avoid pneumothorax.…”
Section: Discussionsupporting
confidence: 78%
“…The American College of Chest Physicians and BTS guidelines recommend diagnostic flexible bronchoscopy under conscious sedation (4,5). Bronchoscopy under conscious sedation with a combination of midazolam with fentanyl in this study could be safely performed and confirmed the previous study (12). Conscious sedation may lead to avoid pneumothorax.…”
Section: Discussionsupporting
confidence: 78%
“…Studies from other parts of the world also suggest that sedation technique performed by nonanesthesiologists during bronchoscopy is safe and cost-effective. 1,8,14 The major side effect was observed in two of our patients and both patients recovered fully. One patient needed brief endotracheal intubation and mechanical ventilation and the second patient required ICU monitoring for a sudden rise in blood pressure (20% of baseline) which improved spontaneously within 1 hour.…”
Section: Discussionmentioning
confidence: 54%
“…Two prospective studies have demonstrated that sedation could be safely administered by a nonanesthesiologist without increased risk of complications. [121122] In a survey done in Switzerland among 229 pulmonologists, it was found that in 84% of bronchoscopies, propofol was administered without anesthesiologist and sedation-related morbidity and mortality were low. [123] Although propofol administered by a trained physician has been found to be safe, it must be remembered that it is a respiratory depressant with a narrow therapeutic range and has no available reversal agent.…”
Section: Premedicationmentioning
confidence: 99%